PENINGKATAN KINERJA KARYAWAN MELALUI STRATEGI KOMPENSASI DAN GAYA KEPEMIMPINAN DI PT. CWLI - Bambang Fajarisman (KELOLA: Jurnal Ilmiah Manajemen, 2022)
This study aims to find the dominant factors that affect the level of employee performance at PT. CWLI. Employee performance level is an absolute goal that must be achieved by every business organization. The level of employee performance is the main trigger in moving the business organization by optimizing the competencies possessed by employees. If the factors that affect the level of employee performance can be identified, the employee's performance level can be measured, assessed, and planned for other business expansion activities. This research uses quantitative methods. The population used in this research is 65 people who are employees of PT. CWLI and the number of samples is 64 respondents. Sampling using random sampling technique (random sampling). The data analysis method uses regression analysis and the results of this study state as follows, 1) the compensation variable has a significant positive effect on the performance of the employees of PT. CWLI. 2) the leadership style variable has a significant positive effect on the performance of the employees of PT. CWLI. 3) simultaneously the compensation and leadership variables have a significant positive effect on the performance of the employees of PT. CWLI.